DETERMINING THE EFFICIENCY OF EXPERT ASSESSMENT PROCEDURES FOR THE CREATION OF NORMAL DOCUMENTS OF A CUSTOM AVIATION - Литвин, А. М.; Соломенцев, О. В. (Proceedings of National Aviation University (archive), 2020)
The analytical relations for the reliability of the classification of proposals proposed by experts during the work on creation of normative documents of civil aviation are presented.